2019
DOI: 10.1111/imj.14392
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Montreal Cognitive Assessment and Rowland Universal Dementia Assessment Scale in a multicultural rehabilitation setting

Abstract: In Australia it is recommended that all older people undergoing rehabilitation have a cognitive screen. We performed a longitudinal study comparing the correlation of two cognitive screening tools – the Rowland Universal Dementia Assessment Scale (RUDAS) and Montreal Cognitive Assessment (MoCA) with discharge outcomes in a geriatric inpatient setting. The RUDAS cut‐off (<23/30) was associated with discharge to a nursing home (sensitivity 52%, specificity 70%). This was also noted with a MoCA cut‐off <18/30 (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…This study directly compared the diagnostic properties of the RUDAS-Thai and the MoCA-Thai in screening MCI among older adults in an outpatient setting where most studies focused their performance on screening dementia [ 21 , 22 , 23 , 36 , 37 ]. The finding of this study supports that the RUDAS score was moderately correlated to the MoCA score [ 25 ]. The results show that the overall performance of both tests was indifferent according to the AUC of the ROC curve.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study directly compared the diagnostic properties of the RUDAS-Thai and the MoCA-Thai in screening MCI among older adults in an outpatient setting where most studies focused their performance on screening dementia [ 21 , 22 , 23 , 36 , 37 ]. The finding of this study supports that the RUDAS score was moderately correlated to the MoCA score [ 25 ]. The results show that the overall performance of both tests was indifferent according to the AUC of the ROC curve.…”
Section: Discussionsupporting
confidence: 87%
“…One longitudinal study in a multicultural rehabilitation setting in Australia which studied the association of the MoCA and the RUDAS with discharge outcomes showed that the RUDAS at <23/30 and the MoCA at <18/30 were related to nursing home placement (sensitivity of 52% and 57%, and specificity of 70% and 69%, respectively). There was a moderate correlation between those two tests (r = 0.571), and the RUDAS appeared to have a briefer administration time in both English- and non-English-speaking backgrounds [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…RUDAS was found to be as accurate as the MMSE [ 14–16 ], with a similar sensitivity (range: 52–94%) and better specificity (range: 70% –98%) [ 17 ]. Area under the curve (AUC) values reported ranged between 0.62 [ 18 ] to 0.93 [ 19 ]. The majority of studies showed that RUDAS scores were found to be uninfluenced by education [ 16 ], language [ 16, 20 ], and sex [ 16 ]; however, three studies identified that RUDAS scores were influenced by education, as highlighted in Table 2 [ 14, 17, 19 ].…”
Section: Resultsmentioning
confidence: 99%